Real-world outcomes and treatment patterns in Colombian patients with neovascular age-related macular degeneration and diabetic macular edema - Joshua Kock; José D. Miranda; Farley Johanna Gonzalez-Patino; Sebastián Rojas; Luz E. Pérez; Jhon Edwar Bolaños; Carlos J. Bello; Jose D. Manga; Mauricio A. Hernández; Laura Prieto-Pinto (The Pan-American Journal of Ophthalmology, 2025)
Background/Objectives: Neovascular age-related macular degeneration (nAMD) and diabetic macular edema (DME) are the leading causes of vision loss worldwide, with significant public health implications in middle-income countries such as Colombia. Subjects and Methods: This retrospective study analyzed the sociodemographic, clinical, and treatment characteristics of patients with nAMD and DME over a 10-year period. Antivascular endothelial growth factor therapies, the primary treatment for both conditions, were evaluated for adherence and visual acuity (VA) outcomes in a real-world clinical setting. Results: Mean (±standard deviation) injection rates for nAMD were 4.45 (±2.56) for aflibercept and 4.28 (±2.53) for ranibizumab, while DME rates were 4.87 (±3.10) and 4.62 (±2.99), respectively. Among eyes that completed the loading dose, the annual injection rates exceeded five, with VA gains of +2.73 letters (95% confidence interval [CI]: +2.04 to +3.41) on average. Substantial improvements were observed in patients with severe baseline impairment (≥20/200), gaining +12.5 letters (95% CI: +11.4 to +13.7). Conclusion: The findings emphasize the importance of adhering to recommended treatment regimens and suggest that strengthening patient education and logistical support, alongside novel therapies, could improve adherence and long-term visual outcomes for patients with these conditions in Colombia.